ARISTOLOCHIA BRACTEOLATA – ANTIHYPERGLYCEMIC AND ANTIHYPERLIPIDEMIC ACTIVITY IN DEXAMETHASONE-INDUCED DIABETIC RAT MODEL - Rajum, Ganga; Reddy T, Hema Sundar; Reddy T, Hema Sundar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was aimed to evaluate antihyperglycemic and antihyperlipidemic activities of methanolic extract of Aristolochia bracteolata (MEAB) against dexamethasone-induced diabetic rat model. Methods: Methanolic extract was prepared by soxhlet extraction and was evaluated for antihyperglycemic and antihyperlipidemic activity using dexamethasone-induced model. The MEAB was administered orally at a dose of 200 and 400 mg/kg body weight glibenclamide was used as standard drug. On 0th and 11th day, blood was collected by retro-orbit plexus. Results: In this model blood glucose levels were determined on 0th and 11th days and MEAB significantly reduced the blood glucose levels in diabetic rats. The effect of MEAB on serum lipid profile such as total cholesterol (TC), triglycerides (TGs), low-density lipoprotein (LDL), very LDL (VLDL), and high-density lipoprotein (HDL) was also measured on the 11th day in the diabetic rats. Significant reduction in TC, TGs, LDL, and VLDL levels and improvement in HDL level were observed in diabetic rats. Conclusion: From the results, it was found that the MEAB possess antihyperglycemic and antihyperlipidemic activities.